Analisis Pengaruh Pembiayaan Musyarakah, Dana Pihak Ketiga Terhadap Profitabilitas Bank Sumut Syariah Medan - ridwan, Muhammad; M.Abrar Kasmin Hutagalung; Bagus Riski; Riswan Rambe (IAIN Langsa, 2024)
This research aims to examine the impact of musharaka funding and funding from third parties on profitability. The data used includes the Financial Report of PT Bank Sumut Syariah KC Medan for a four year period (2015-2018), which consists of 48 monthly reports. The data analysis method used is multiple linear regression analysis. The results show that both musharaka funds and Third Party Funds (DPK) have a substantial and beneficial impact on profitability when analyzed together. (F-test). This is supported by an adjusted R-squared value of 10%. The T-test reveals that the T-calculated value for musyarakah finance as an independent variable is 2.329, which exceeds the T-table value of 2.012 (2.329 > 2.012). This shows a positive and statistically significant impact on profitability. On the other hand, the T-calculated value for the independent variable of third-party funds is -0.524, which is less than the T table value of 2.329 (-0.524 < 2.329). Additionally, the p-value of 0.603 exceeds the critical value of 0.05, resulting in acceptance of the null hypothesis. (H0). This means that third-party funds do not have a statistically significant effect on profitability. These findings show the importance of improving musyarakah financing services to increase the profitability of Bank Sumut Syariah.